AIR EXCHANGE SYSTEM IN ENERGY-EFFICIENT BUILDINGS (Academicia Globe: Inderscience Research, 2022)
This article is a brief overview of the ventilation system of buildings, the importance of ensuring air exchange. Energy-efficient methods of air exchange of buildings. It was told about the concept of air exchange, their advantages and disadvantages. Brief information about the types of air exchange is given..